Potret Lokalisasi Gang Dolly dalam Perspektif Patologi Sosial - Akmal Saputra (Jurnal Community, 2015)
Prostitution, localization and freesex is a phenomenon that is familiar in the midst of the people of Indonesia, including the case "Gang Dolly" that attracted public attention in the last year. “Gang Dolly” has been established since the Dutch colonial era and the largest in Southeast Asia and one brothel that gets the legality of the government. Gang Dolly is a social problem that can be analyzed in various perspective, one of them is in pathological perspective.  The adverse effect of localization "Gang Dolly" is not only felt by men and women but including The children feel the effects, either psychological aspect or others. The cause of women's involvement in prostitution can be caused by social conditions of local communities or pathological conditions that result in individuals becoming pathological, but it is also due to structural dysfunction. Closure "Gang Dolly", mitigation and prevention needs to be done and has been done by the government of the city of Surabaya, the hope is to make the public should be able to re-live human being who is far from pathological conditions and become a religious community.